Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serious Games on Health and Well-being of Elderly: A Systematic Review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…In particular, participants' outcomes indicated an overall improvement in well-being levels from the beginning until the end of the intervention, between the first and fifth evaluation, while an initial improvement was already observed between the first and the second evaluation of older adults ageing 71 and higher [7,16]. This improvement is possibly related to the exploitation of new technologies and serious games, which contribute to increasing aspects of quality of life, and, in particular, they have a positive effect on participants' proactivity in their daily lives [17]. The results also seem to have a connection between the age of the examined population and the effect of experiencing events, which is associated with intrusive emotions and thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, participants' outcomes indicated an overall improvement in well-being levels from the beginning until the end of the intervention, between the first and fifth evaluation, while an initial improvement was already observed between the first and the second evaluation of older adults ageing 71 and higher [7,16]. This improvement is possibly related to the exploitation of new technologies and serious games, which contribute to increasing aspects of quality of life, and, in particular, they have a positive effect on participants' proactivity in their daily lives [17]. The results also seem to have a connection between the age of the examined population and the effect of experiencing events, which is associated with intrusive emotions and thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…Exergaming has been limitedly studied among older adults. Whilst there are numerous studies conducted with older adults as participants, they have mostly been related to physical and wellness aspects, balance and falls prevention, or rehabilitation (Nguyen et al, 2017), with only a few touching the subject of user experience (e.g., Loos, 2017;Pyae et al, 2016). Overall, the related findings have been promising.…”
Section: Exergamingmentioning
confidence: 99%
“…Overall, the related findings have been promising. For example, the systematic review by Nguyen et al (2017) concluded that 75% of the reviewed papers found games to have positive impacts on the well-being of the elderly. Stanmore et al (2019) conducted an exergaming intervention for people aged 55 years and older and concluded that exergames may be used to improve balance, reduce pain and the fear of falling, and are a cost-effective fall prevention strategy in assisted living facilities.…”
Section: Exergamingmentioning
confidence: 99%
“…Initial teacher feedback was very positive and supportive of the research direction [11]. On the other hand, use of digital games as a tool for health improvements in elderly population [12] has proven to have beneficial effects especially on their cognitive health although seniors might show lack of initial motivation in performing such tasks.…”
Section: Introductionmentioning
confidence: 99%